Mengoptimalkan Kualitas Layanan: Dampak Implementasi SOP Dalam Layanan Jasa Kurir - Parhan Parhan; Raisya Amalia Burhannudin (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
This study aims to analyze the impact of implementing Standard Operating Procedures (SOP) on the service quality of PT. Tiki Jalur Nugraha Ekakurir (JNE) delivery services. The results show a positive influence of SOP implementation on the service quality of JNE's delivery services. Clear and easily understood SOPs help JNE employees complete tasks consistently and efficiently, reducing the likelihood of errors and omissions. Additionally, employee commitment and discipline in applying SOPs, along with support and supervision from management, are crucial in improving service quality. The suitability of SOPs with the needs and conditions of the company is also a key aspect to be considered. Based on these findings, it is recommended that JNE continuously improve the quality of its SOPs and ensure their implementation by employees. Furthermore, enhancing other factors such as infrastructure, technology, and human resources is essential to achieve sustainable excellent service.